Optimizing Employee Communication Skills To Enhance Service Quality In The Front Office Department Of Radisson Blu Hotel Bali Uluwatu - Tagah, Ferensia Resita; Takaendengan, Mita Erdiaty; Lumettu, Agustinus (Politeknik Sahid, 2024)
In the current era of globalization, business competition in the tourism industry is becoming increasingly fierce. One of the critical factors in attracting consumer interest is the quality of service. Communication skills are the ability to convey information clearly and effectively to others. In the context of service, good communication skills help employees understand the needs and desires of consumers, thus providing service that meets expectations.Purpose: of this study that is optimize the communication skills of employees in the Front Office Department at Radisson Blu Bali Uluwatu Hotel to improve service quality.Methods: of This study employs a descriptive qualitative method to determine the research results.Implications: Interviews with three receptionists, each answering five identical questions, revealed that communication skills need to be continuously enhanced to improve the quality of service at the hotel.Observations of 4 employees showed poor results in several aspects, such as politeness in speech, tone of voice, and English proficiency, indicating that communication skills in the Front Office Department of Radisson Blu Bali Uluwatu Hotel still need significant improvement. Good communication skills are essential for Front Office employees, as they represent the first point of interaction between guests and the hotel. Optimal communication quality can enhance a guest's first impression, influence their level of satisfaction, and strengthen customer loyalty. High-quality service in a hotel depends on how well employees can effectively respond to guest needs. Good communication ensures that messages are conveyed clearly and promptly, minimizing misunderstandings and improving service efficiency.